Electronic structure and orientation of NO on Ni(111) studied by arups using synchrotron radiation - Steinrück, Hans-Peter; Schneider, C.; Heimann, P.A.; Pache, T.; Umbach, E.; Menzel, Dietrich (Surface Science, 1989)
The electronic structure and the orientation of NO adsorbed on Ni(111) at 120 K was studied by angle resolved UPS using linearly polarized synchrotron radiation and a multichannel angle resolving electron analyzer. The layer investigated corresponds to a coverage of 0.5 ML and exhibits a c(4 × 2) LEED pattern with only twofold bridging sites being occupied. The binding energies for 4 ̃gs, 5 ̃gs and 1 ̃gP at the ḡG point are 15.1, 9.3 and 7.5 eV, respectively; the 1 ̃gP level is very broad which may be due to splitting. The 2D band structure shows a dispersion of 0.3 eV for the 4 ̃gs and 0.6 eV for the 5 ̃gs level, indicative of lateral interactions within the adsorbed NO layer. The photon energy dependence of the photoionization cross sections of the 4 ̃gs, 5 ̃gs and 1 ̃gP NO molecular orbitais has been studied in the energy range 26 eV ≤ ℏgw ≤ 60 eV. The 4 ̃gs level shows a pronounced maximum at ℏω = 36 eV (E = 15 eV) that is peaked in the direction of the surface normal and is interpreted as a shape resonance. For the 5 ̃gs and 1 ̃gP levels no shape resonances are observed. Using dipole selection rules, it is demonstrated independently by initial state and final state arguments that in a c(4 × 2) layer the NO molecules are adsorbed with their molecular axis perpendicular to the surface. © 1989.